The experiences and wellbeing of adults who use cannabis - James, Philip; Comiskey, Catherine (My University, 2024)
Cannabis is the most widely used illicit drug in Ireland with 13.8% of those aged 15-64 consuming it in the past year. Males and younger adults tend to use cannabis more frequently. While not all require treatment, cannabis can have significant health effects
Inclusion Health Nurses Section Conference
PUBLISHED
Dublin
Keywords: Addiction and substance abuse; HARM REDUCTION; Mental health promotion